Gut Microbiome in Retina Health: The Crucial Role of the Gut-Retina Axis - Scuderi, Gianluca; Troiani, Emidio; Minnella, Angelo Maria (Frontiers in Microbiology, 2022)
The term microbiome means not only a complex ecosystem of microbial species that colonize our body, but also their genome and the surrounding environment in which they live. Recent studies support the existence of a gut-retina axis involved in the pathogenesis of several chronic progressive ocular diseases, including age-related macular disorders. This review aims to underline the importance of gut microbiome in relation with ocular health. After briefly introducing the characteristics of the gut microbiome in terms of composition and functions, the role of gut microbiome dysbiosis, in the development or progression retinal diseases, is highlighted, focusing on the relationship between gut microbiome composition and the retinal health based on the recently investigated gut-retina axis.